Effects of the Coronavirus Disease 2019 (COVID-19) Pandemic on Outcomes among Patients with Polytrauma at a Single Regional Trauma Center in South Korea - Sun Hyun Kim; Dongyeon Ryu; Hohyun Kim; Kangho Lee; Chang Ho Jeon; Hyuk Jin Choi; Jae Hoon Jang; Jae Hun Kim; Seok Ran Yeom (Journal of Trauma and Injury)
Purpose The coronavirus disease 2019 (COVID-19) pandemic has necessitated a redistribution of resources to meet hospitals’ service needs. This study investigated the impact of COVID-19 on a regional trauma center in South Korea. Methods We retrospectively reviewed cases of polytrauma at a single regional trauma center in South Korea between January 20 and September 30, 2020 (the COVID-19 period) and compared them to cases reported during the same time frame (January 20 to September 30) between 2016 and 2019 (the pre-COVID-19 period). The primary outcome was in-hospital mortality, and secondary outcomes included the number of daily admissions, hospital length of stay (LOS), and intensive care unit (ICU) LOS. Results The mean number of daily admissions decreased by 15% during the COVID-19 period (4.0±2.0 vs. 4.7±2.2, p=0.010). There was no difference in mechanisms of injury between the two periods. For patients admitted during the COVID-19 period, the hospital LOS was significantly shorter (10 days [interquartile range (IQR) 4–19 days] vs. 16 days [IQR 8–28 days], p<0.001); however, no significant differences in ICU LOS and mortality were found. Conclusions The observations at Regional Trauma Center, Pusan National University Hospital corroborate anecdotal reports that there has been a decline in the number of patients admitted to hospitals during the COVID-19 period. In addition, patients admitted during the COVID-19 pandemic had a significantly shorter hospital LOS than those admitted before the COVID-19 pandemic. These preliminary data warrant validation in larger, multi-center studies.